2020
DOI: 10.1002/mma.6735
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of entropy generation in Williamson fluid flow with nonlinear thermal radiation and first‐order velocity slip

Abstract: This research article investigates the impacts of magnetohydrodynamics (MHD), nonlinear thermal radiation, Darcy‐Forchheimer porous medium, viscous dissipation, first‐order velocity slip, and convective boundary condition on the entropy generation optimization in flow of non‐Newtonian fluid (Williamson fluid) towards a flat and stretchable surface. A general entropy equation is derived for thermal heat irreversibility, porosity irreversibility, Joule heating irreversibility, and fluid friction irreversibility.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…However, they observed that non-Newtonian fluids caused by stretching sheets provide a significant engineering and technological problem because of their widespread engineering and technological applications in a variety of industrial and engineering processes [14][15][16][17][18][19]. In references [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], you can find some additional interesting contributions on Newtonian and non-Newtonian nanofluid flow and its applications in manufacturing. The fundamental purpose of this research is to look at the heat transfer properties of an Eyring-Powell fluid flow caused by a stretching sheet immersed in a porous media and influenced by thermal radiation.…”
Section: List Of Symbols Umentioning
confidence: 99%
“…However, they observed that non-Newtonian fluids caused by stretching sheets provide a significant engineering and technological problem because of their widespread engineering and technological applications in a variety of industrial and engineering processes [14][15][16][17][18][19]. In references [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], you can find some additional interesting contributions on Newtonian and non-Newtonian nanofluid flow and its applications in manufacturing. The fundamental purpose of this research is to look at the heat transfer properties of an Eyring-Powell fluid flow caused by a stretching sheet immersed in a porous media and influenced by thermal radiation.…”
Section: List Of Symbols Umentioning
confidence: 99%
“…The Darcy-Forchheimer number (Fr) must be dimensionless because the terms in Equation 1 are dimensionless. Qayyum et al 1 defined the Darcy-Forchheimer number (Fr) (equation 13 in the paper) as:…”
Section: S C C L a S S I F I C A T I O N Porous Mediummentioning
confidence: 99%
“…Muhammad et al [32] researched the time-dependent squeezing flow of a hybrid nanofluid (having CNTs + CuO/water) and a nanofluid (having CNTs/water) with the melting impact and viscid dissipation to designate the behavior of heat exchange, entropy formation, and bean amount. To optimize the creation of entropy of Williamson fluid flow towards a plain and stretchy surface, Qayyum et al [33] tested the influence of hydromagnetic, nonlinear thermal radiation, Darcy-Forchheimer porous mode, viscous dissipation, 1st-order motion slip, and convective boundary circumstance. To manage the flow system heat transfer, Saeed et al [34] employed the slip conditions created by a whirling disc, thermal stratification, and nonlinear thermal radiation in the solution of the Darcy-Forchheimer flow for TiO 2 -Ag/H 2 O hybrid nanofluid.…”
Section: Introductionmentioning
confidence: 99%